ENVIRONMENTAL AUDITING IN THE PUBLIC SECTOR: MEASURING ACCOUNTABILITY IN GREEN PUBLIC EXPENDITURE - Dewi Nidia Soepriadi; Jabida Latuamury; Kathleen Asyera Risakotta (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyze the role of environmental auditing in the public sector, focusing on measuring the accountability of public expenditure allocated for green or environmentally friendly programs. Using a literature review method, this study examines various academic studies, environmental audit reports, and policy documents related to accountability practices in sustainability-oriented public financial management. The study results indicate that environmental auditing functions not only as a tool for monitoring budget utilization but also as a strategic instrument for ensuring the transparency, efficiency, and sustainability of government environmental policies. The literature analysis demonstrates that integrating environmental audits into public accountability systems can improve the quality of decision-making, strengthen public trust, and promote alignment between fiscal policy and sustainable development goals. However, the study also identifies several challenges, such as limited green performance indicators, insufficient auditor capacity, and weak reporting standards across countries. Therefore, the development of a more comprehensive and standardized environmental audit framework is needed to more effectively measure accountability in green public expenditure and make it comparable across jurisdictions.